Diversity of monogeneans in Southeast Asia. - Lim, L.H. (Elsevier, 1998)
The diversity of monogeneans from Southeast Asia was examined using information from the literature to show their diversity at different taxonomic (subclass, family, genera, species) levels. Knowledge of monogeneans is still incomplete in Southeast Asia and the present numbers of monogeneans are likely an underestimate of what is present on/in aquatic organisms in the region, since so few hosts have been examined. An estimate of the possible numbers of monogeneans that could be present on/in fishes and turtles in Peninsular Malaysia indicates that only 8% of the monogeneans are presently known. Analysis of the available data on monogenean diversity (or species richness) at different taxonomic levels will provide useful information on their distribution patterns. There is an uneven distribution of investigations on this topic and Malayan fauna is considered to be representative of the Southeast Asian fauna. Southeast Asian (Sundaland) monogeneans are related (at the generic level) to the monogenean fauna of South China, India and Africa.